The taxonomic status of Lepus melainus (Lagomorpha: Leporidae) based on nuclear DNA and morphological analyses - Liu, Jiang; Chen, Peng; Yu, Li; Wu, Shi-Fang; Zhang, Ya-Ping; Jiang, Xuelong (Zootaxa, 2011)
The taxonomic status of the species Lepus melainus, the Manchurian black hare, is intensely debated. It is considered either as a valid species or a black color morph of L. mandshuricus, the Manchurian hare. Herein, we evaluate the validity of L. melainus using 24 morphological traits and two nuclear DNA loci (TG=466bp; MGF=592bp) from newly collected specimens. Except for winter pelage, we fail to discover significant morphological differences between L. melainus and L. mandshuricus. Analysis of the nuclear DNA sequences reveals lack of reciprocal monophyly between L. mandshuricus and L. melainus, as they form one single clade with high bootstrap support; in addition, morphometric and morphological analyses found no specific differentiation between forms corresponding to L. mandshuricus or L. melainus. Together with the fact that the range of L. melainus is completely within that of L. mandshuricus, our study supports the recognition of L. melainus as a melanistic morph and junior synonym of L. mandshuricus.